The accuracy of pulmonary ultrasound in the diagnosis and monitoring of community-acquired pneumonia in women of childbearing age - Jun Wang; Xiao-Dong Zhao; Gang Wang; Wei-Ming Li; Hua Guo; Jia-Mei Gou; Guo-Juan Feng; Jing Rao (IMR Press, 2021)
Objective: To evaluate the accuracy of pulmonary ultrasound in the diagnosis of community-acquired pneumonia (CAP) in women of childbearing age. Methods: From June 2014 to July 2018, a total of 275 suspected CAP patients (20-45 years old) were enrolled, including 87 pregnant women and 188 non-pregnant women. All subjects underwent lung ultrasonography at admission, and non-pregnant women also underwent chest X-ray and pulmonary CT examination. CT-positive patients were treated with 7-10 days of anti-infective treatment, and the results of chest X-ray, lung ultrasound, and chest CT were reviewed. Lung consolidation with pneumonia morphological features was evaluated and compared with CT. Results: Of the 188 non-pregnant patients, 48 were diagnosed with CAP. Pulmonary ultrasonography, chest X-ray and lung CT diagnosis of CAP were almost identical (kappa coefficient was 0.691, 0.578, respectively). After 48 days of anti-infective treatment in 48 non-pregnant women, the sensitivity, specificity and positive release ratio of pulmonary ultrasound for pneumonia were 10.923 and 13. Among the 87 pregnant women with suspected CAP, 32 were positive in pulmonary ultrasonography, 7 were positive in pulmonary ultrasound after 7-10 days of treatment, and pregnant women with CAP were admitted to the hospital and treated with ultrasound. There was no statistical difference in ultrasound. Conclusion: Pulmonary ultrasound can be used as the primary means of diagnosing CAP in women of childbearing age.